(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the information era, enormous amounts of data have become available on hand to decision makers. Big data refers to datasets that are not only big, but also high in variety and velocity, which makes them difficult to handle using traditional tools and techniques. It commences with the concept of the subject in itself along with its characteristics and the two general approaches of dealing with it. The comprehensive study further goes on to elucidate the applications of Big Data in all diverse aspects of economy and being. Beside this, the incorporation of Big Data in order to improve population health, for the betterment of finance, telecom industry, food industry and for fraud detection and sentiment analysis have been delineated and different trends in big data is also discussed.